Strengthening Principals’ Growth Mindset to Support Deep Learning - Arifin Nur Budiono; Yurike Kinanthy Karamoy (DEVOTIONIS, 2026)
This community service program was conducted to strengthen school principals’ growth mindset as a foundation for instructional leadership in supporting the implementation of Deep Learning. The background of this program was the need for school leaders to develop adaptive, reflective, and growth-oriented perspectives in responding to educational change, particularly in fostering mindful, meaningful, and joyful learning environments. The program aimed to enhance principals’ understanding and readiness to apply growth mindset principles in their leadership practices. The activities involved 32 principals from elementary schools and early childhood education institutions in Jember Regency and were implemented through an andragogy-based training and mentoring approach. The methods included interactive lectures, classroom discussions, reflective worksheet activities, group presentations, and collaborative learning strategies designed to encourage reflection, dialogue, and shared learning experiences among participants. The results indicated that the program successfully facilitated conceptual understanding and initial behavioral changes among participants. Principals demonstrated increased active participation, openness to feedback, reflective thinking, and readiness to implement follow-up actions related to Deep Learning in their respective schools. In addition, the program produced reflective learning artifacts and contributed to the emergence of an initial professional learning network among principals, supporting peer collaboration and knowledge sharing. In conclusion, the community service program effectively achieved its objectives by strengthening principals’ growth mindset through participatory and reflective learning processes, suggesting that growth mindset-based leadership development constitutes a relevant and sustainable strategy for enhancing instructional leadership and supporting the implementation of Deep Learning in schools.